Perice v Boljuncu - Repinc, Martina (Etnolog. Nova vrsta (Ljubljana), 2001)
The articles deals with the washerwomen from Boljunec near Trieste, the village where this service survived the longest. Some of them did the laundry for their clients until the late 1970s. The research is based on oral information and deals with the weekly working cycle (collecting, soaking, washing, rinsing, drying and returning the laundry). The article also presentsthe difficulties women met in carrying out their job (customers, the foreign town, language).
Keywords: ethnology; etnologija; Trst; woman; ženske; obrti; perice; zamejski Slovenci; Boljunec